Emotional Labor Demands, Wages and Gender: A Within-Person, Between-Jobs Study - BHAVE, Devasheesh P. (Institutional Knowledge at Singapore Management University, 2009)
Although research suggests the important role of gender in emotional labour, its effect on the relationship between emotional labour demands and wages has not been examined explicitly. The current study investigates this relationship by testing hypotheses derived from theories of vocational choice and labour market supply and demand. Hypotheses are tested using a unique within-person, between-jobs longitudinal dataset with information on two jobs for each worker in a national sample of U.S. workers (N=5,488). After controlling for relevant variables related to wages, results suggest men incur wage penalties of approximately 6% when moving to occupations with higher emotional labour demands. Women do not experience statistically significant wage effects from moving to an occupation with higher emotional labour demands. These findings are discussed and interpreted based on the theoretical frameworks.